Limits of an "Energy Union": Only pragmatic progress on EU energy market regulation expected in the coming months - Severin Fischer; Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2015)
Since the Juncker Commission took office in late 2014, the idea of an »Energy Union« has been a central theme of the EU energy policy debate. Today, the Energy Union concept covers every area of current European energy and climate policy. Its primary objective is to create a coherent, overarching policy framework. From a political perspective, the Commission's aim is to prevent any further renationalization of energy policy. But although the Member State governments constantly refer to the energy union concept, it is already clear that they will avoid or at least delay implementation of meaningful steps in the direction of such a union. Against this backdrop, it is unlikely that any fundamental changes will take place in the near future. And over the next few years, the focus of EU energy and climate policy will be on pragmatic progress in the area of energy market regulation-not on strategic large-scale projects. (SWP Comments)
Keywords: 320